Dynamic Modelling and Control of Thermal Energy Storage. (February 2019) - Bastida, Hector; Ugalde-Loo, Carlos E.; Abeysekera, Muditha; Qadrdan, Meysam; Wu, Jianzhong; Jenkins, Nick
Abstract: Thermal energy storage (TES) is a critical element in district heating systems and having a good understanding of its dynamic behaviour is necessary for effective energy management. TES supports heat sources in achieving a steady power supply. Achieving heat and electric load demand translates into a discharging and charging control problem in terms of stored heat energy. To this end, an accurate dynamic model is essential to design effective controllers to improve district heating performance. A thermal dynamic model of a water tank, together with controllers for energy charging and discharging processes, are presented in this paper. The model is based on a computational fluid dynamics approach. It is developed using thermal stratification. The hot or cold-water stream which vertically crosses each tank section is considered to describe heat transfer. This is a non-linear process represented by partial differential equations, which are linearised to obtain a suitable model for control system design. State-space and transfer function representations of the system are obtained. The non-linear model is implemented in MATLAB/Simulink to design a linear controller that regulates the mass flow rate of cold and hot water to fill or empty the tank's energy according to performance specifications. The design of regulation and tracking controllers is explained. Simulation results show that a good performance in terms of the mass flow rate input demands is achieved with the proposed controllers.